Socio-economic determinants and adoption of pest management practices in cashew farming: A study in Dakshina Kannada, Karnataka - P.L. Saroj, M.V. Sajeev, (Journal of Plantation Crops, 2018)
The existing technology utilization status and its socio-personal and economic determinants with respect to adoption of recommended pest management technologies were studied among cashew farmers in Dakshina Kannada district of Karnataka by using an ‘ex-postfacto cause to effect’ design. The findings denoted poor adoption index (20) with particularly high non-adoption for pest management of cashew stem and root borer (CSRB). The correlation analysis identified seven variables viz., farming experience (years), extension participation, importance given to cashew crop, number of yielding cashew trees, expenditure incurred in agriculture, net income from agriculture and net income from cashew farming as having significant relationship with farmers’ adoption of pest management technologies. The regression analysis revealed three variables, the age of cashew farmer, their primary occupation and farm size as contributing significantly in explaining the adoption of pest management technologies. The variables used in the study could together explain up to 60 per cent variability in adoption of pest management technologies. The stepwise regression model developed to predict adoption rate of pest management practices explained up to 46.4 per cent of the variation in adoption of pest management technologies using the predictors; number of cashew trees (X1), years of experience in farming (X2), ICT usage (X3), primary occupation of farmer(X4), income from agriculture (X5) and age of the farmer (X6). Understanding the technology utilization process in cashew can help researchers and development agencies working in cashew sector to evolve better technologies for pest management.